Effects of HIV infection on metastatic cervical cancer and age at diagnosis among patients in Lusaka, Zambia. Issue 3 (14th July 2021) - Trejo, Mario Jesus; Soliman, Amr S.; Chen, Yuli; Kalima, Mulele; Chuba, Alick; Chama, Eslone; Mwaba, Catherine K.; Banda, Lewis; Lishimpi, Kennedy
Abstract: Objective: To examine the association between the duration of HIV infection and the stage of cervical cancer in Lusaka, Zambia. Methods: This retrospective case‐case study included 1583 cervical cancer patients from the Cancer Diseases Hospital in Lusaka, Zambia. A sub‐population of HIV‐positive patients with additional clinical HIV information was identified following linkage of cancer and HIV databases. Logistic regression models examined the relationship between HIV status and early‐onset cervical cancer diagnosis, and between HIV infection duration and initial diagnosis of metastatic cervical cancer. Results: The study population had an average age of 49 years and 40.9% had an initial diagnosis of metastatic cancer. HIV‐positive women were more than twice as likely to be diagnosed at early‐onset cervical cancer compared with HIV‐negative women. Among the sub‐population of HIV‐positive patients, a longer duration of HIV infection was associated with 20% lowered odds of initial metastatic cancer diagnosis. Conclusion: The availability, accessibility, and impact of the cervical screening program in this population should be further examined to elucidate the relationship between cervical screening, age, and duration of HIV infection and the the stage of diagnosis of cervical cancer. Abstract : HIV status was associated with early‐onset cervical cancer. However, a longer duration of HIV infection was associated with decreased odds of metastatic cervical cancer.